Optimizing New Product Development in Automotive Manufacturing: The Role of DFMA in Multi-Purpose Vehicle Production - Ariyani, Made Laksmi; Karningsih, Putu Dana; Wicaksono, Bagas Wahyu; Syamsuri, Ahmad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the application of Design for Manufacturing and Assembly (DFMA) principles to enhance the production process of Multi-Purpose Vehicles (MPVs). The research aims to improve assembly efficiency and reduce manufacturing costs by evaluating and modifying the existing MPV design. By eliminating unnecessary components, such as Bolt Type 1, PU Box, Rear Cabin, and Bolt Type 2, and incorporating fit-in technologies like snap-fit mechanisms, the design is simplified to streamline the assembly process and reduce complexity. DFMA software analysis, along with design modifications, shows a substantial reduction in assembly time and cost, while improving product reliability. The findings demonstrate how DFMA can enhance the manufacturability of MPVs, providing an effective strategy for manufacturers to stay competitive in the automotive sector. The study also underscores the importance of iterative design evaluation and re-evaluation in achieving optimal product quality and operational efficiency. This research offers practical insights into applying DFMA in automotive product development and sets the foundation for further studies on its impact in other industries